Aeromonas in Arab countries: 1995–2014. (October 2015) - Ghenghesh, Khalifa Sifaw; Rahouma, Amal; Zorgani, Abdulaziz; Tawil, Khaled; Al Tomi, Abdurazzaq; Franka, Ezzadin
Highlights: Data from English language literature search from 1995 to 2014 of Medline/PubMed. Aeromonas spp. were isolated from diarrheal children, animals, foods and waters. Cephalosporins and fluoroquinolones are effective against Aeromonas infections. More studies employing molecular testing methods are required in future. Microbiologists in the region should look for these organisms in different sources. Abstract: The aim of this review is to provide information on the prevalence, clinical syndromes, and antimicrobial resistance and therapy of Aeromonas spp. infections in Arab countries. The data were obtained by an English language literature search from 1995 to 2014 of Medline and PubMed for papers using the search terms " Aeromonas + name of Arab country (i.e. Algeria, Egypt, etc.)". Additional data were obtained from a Google search using the aforementioned terms. The organisms have been reported from diarrheal children, patients with cholera-like diarrhea, an outbreak of acute gastroenteritis and from different types of animals, foods and water source in several Arab countries in the Middle East and North Africa with predominance of A. hydrophila, A. caviae and A. sobria . Using molecular techniques few studies reported genes encoding several toxins from aeromonads isolated from different sources. Among the antimicrobials examined in the present review third generation cephalosporins, fluoroquinolones and aminoglycosides showed excellent activity and can be employed in the treatment of Aeromonas -associated human infections in Arabic countries. Whenever possible, treatment should be guided by the susceptibility testing results of the isolated organism. In the future, studies employing molecular testing methods are required to provide data on circulating genospecies and their modes of transmission in the community, and on their mechanisms of resistance to antimicrobials. Microbiology laboratories and research centers are encouraged to look for these organisms in clinical, food and water sources to attain a better understanding of the public health risks from these organisms in Arab countries.